Palliative chemotherapy for advanced gastric cancer - Wöhrer, S. S.; Raderer, M.; Hejna, M. (Annals of oncology, 2004)
Background: More than two-thirds of patients diagnosed with gastric cancer will have unresectable disease. They present a difficult problem to clinicians as to whether to choose a strictly supportive approach or expose patients to the side-effects of a potentially ineffective treatment. The objective of this article is to review the clinical trials utilizing cytotoxic chemotherapy in patients with advanced gastric cancer. Methods: A computerized (Medline) search was carried out to identify papers published on this topic between 1966 and 2003. Only articles with an English abstract were reviewed, and studies only presented in abstract form were not included in the analysis. Results: A total of 101 trials were subsequently identified. Four randomized trials compared palliative chemotherapy with best supportive care in 174 patients with advanced gastric cancer. Effectiveness and side-effects were evaluated in 73 phase II studies and 24 randomized phase III trials. Conclusion: Analysis of results shows chemotherapy to be superior to best supportive care alone. Combination chemotherapy compared with monochemotherapy is associated with significantly higher overall (complete plus partial) response rates but nevertheless results in similar survival. ECF (epirubicin, cisplatin and 5-fluorouracil) currently represents one of the most effective regimens for advanced gastric cancer, whereas among the newer combinations, irinotecan- or taxane-based regimens have also given promising results. In patients with a poor performance status, consideration could be given to leucovorin-modulated 5-fluorouracil alone. Prognosis for the majority of patients, however, remains poor, as increases in survival were moderate at best.